The Impact of Interventions Based on Mishel’s Uncertainty in Illness Theory on Caregivers of Children Diagnosed with Cancer: Randomized Controlled Trial - Fatma Taş Arslan; Sevil Özkan (Genel Tıp Dergisi, 2022)
Aim: To investigate the effects of nursing interventions based on Mishel’s Uncertainty in Illness Theory (MUIT) on uncertainty, hopelessness, coping and adaptation for care givers of children diagnosed with cancer.